A Parallel Polyurea Method for Enhancing Damping Characteristics of Metal Lattice Structures in Vibration Isolation and Shock Resistance - Zhongyi Cheng; Xinbin Zhang; Yizhong Zhuang; Yamin Zhao; Junning Cui (Applied Sciences)
The inherent damping deficiency in metal lattice structures leads to inadequate attenuation of both resonant peaks and shock-induced vibrations, significantly limiting their effectiveness in vibration isolation and shock resistance applications. To address this limitation, we developed a novel parallel polyurea method that utilizes the viscoelastic energy dissipation mechanism of polyurea to substantially improve structural damping performance. The metal lattice–polyurea parallel vibration isolation system was designed with its theoretical model established to characterize damping properties, vibration isolation, and shock-resistant performance. An experimental setup was developed to validate theoretical predictions through controlled semi-sinusoidal shock and swept-frequency tests. Experimental results demonstrate excellent agreement with theoretical predictions. The introduction of the polyurea damping structure significantly enhances the system’s damping performance. Compared to the conventional metal lattice isolator, the proposed metal lattice–polyurea parallel composite structure shows remarkable damping improvements: under shock excitation, it achieves substantial attenuation of peak response amplitude with accelerated decay rate, while under frequency-sweep excitation, it maintains the original resonance frequency but reduces the transmissibility peak significantly.